BIOCONTROL OF PARASITES IN RUMINANTS WITH FUNGI - Ojeda Robertos, Nadia Florencia; Rodríguez Vivas, Roger Iván; Peralta Torres, Jorge Alonso (Kuxulkab’, 2022)
Fungi are living organisms with some species that act as natural enemies of livestock parasites and can be used to control populations of ticks, flies and gastrointestinal worms. The control of gastrointestinal nematodes with the micro-fungus, ’Duddingtonia flagrans’, reduces the parasitic burden of grasslands by trapping and feeding the infective larvae of gastrointestinal worms. Another fungus, ’Metarhizium anisopliae’, in field studies reduced the larval tick population in grasslands by 64-100 %. Likewise, ’M. anisopliae’, and ’Isaria fumosorosea’ were shown to control the horn fly ’Haematobia irritans’ by 94-100 % and 90-98 %, respectively. This document discusses how fungi damage parasites and its future use in an integrated parasite control in ruminant livestock.